The penetration efficiency of a dissolved model drug into hair follicles depends on the concentration of added nanoparticles - Loris Busch; Darya Asadzadeh; Anna Lena Klein; Phuvamin Suriyaamporn; Mont Kumpugdee Vollrath; Cornelia M. Keck; Martina C. Meinke (Drug Delivery and Translational Research, 2025)
Hair follicles have recently emerged as promising drug delivery targets and gates for skin penetration. The so-called ratchet effect, which is based on an interaction between the hair shaft surface, the intrafollicular stratum corneum and nanoparticles, has proven to be very effective for the transport of active ingredients. Especially the nanoparticle-assisted decolonization of hair follicles constitutes an interesting new area of application. In a recently published work it was shown that small molecules as well as macromolecules solved in an outer phase of a formulation can be transported into the deeper parts of the hair follicles by adding nanoparticles to the formulation. In this case the nanoparticles constitute an entity independent of the drug and the transport is hypothesized to be based on an adhesion effect. In the present work, we focused on the impact of the particle concentration in the formulation on the transport efficiency of the model drug fluorescein sodium into hair follicles utilizing an ex vivo porcine skin model. It was observed that a particle concentration of 4% significantly enhances the transport efficiency of fluorescein as compared to 2% particle concentration. Doubling the concentration to 8% did not significantly increase the penetration depth. The effect evolved more efficiently when using 4 Hz circular motion massage as compared to 100 Hz oscillating massage. These results deliver interesting information on the optimal formulation as well as application parameters for a future application in clinical studies for e.g. skin antisepsis purposes. Graphical abstract